(untitled) (Proceedings of the International Conference on Agriculture, 2022)
Plant genetic resources are a collection of potentially useful genetic material that is found both within and between certain taxonomies. A good understanding of their distribution is necessary to protect the plant genetic resources for food and agriculture. Understanding the locality of the collected and conserved sorghum landraces in South African gene bank’s germplasm core collection is therefore critical. The study, therefore aimed at mapping and quantifying the geographic distribution of sorghum landraces in germplasm core collection of the South African gene bank from 1996 to 2008. 312 sorghum landraces were collected and conserved in South African gene bank between 1996 and 2008. The geographical location of 152 villages in 57 municipalities, located in 23 District Municipalities of six (6) Provinces, was used to generate a spatial distribution of Sorghum accessions. The sorghum collections in the South Africa gene bank core collection revealed an important dispersion, covering different geographic areas, with the majority (40.1%) of collections made in Limpopo Province for a period of 12 years. It was observed that in 2003, the sorghum collection increased by more than three time the initial collection in 1996. In contrast, there was a decreasing trend of sorghum collection observed between 2003 and 2008. Crop diversity may be necessary for future climate adaption, and its conservation is dependent on human activities and performance. The current analysis is also valuable in identifying collection priority locations, both explored and unexplored. Between 1996 and 2008, there were changes in the geographical distribution of sorghum germplasms in South Africa, which might be related to changes in climatic and agronomic conditions, the introduction of new varieties, and/or the development of new agricultural practises.